2006
DOI: 10.1111/j.1479-828x.2006.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

First trimester medical termination of pregnancy: An alternative for New Zealand women

Abstract: Background: First trimester medical terminations of pregnancy (TOP) have been carried out in a private abortion clinic in Auckland

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In 14 office-based studies, <0.1% [30] to 8.0% [22] of abortions required repeat aspiration, primarily for retained products of conception, although Thonneau et al [24] did not explicitly report this intervention for the 14 women with retained tissue at follow-up (Table 2). Repeat aspiration ranged from 0% [57] to 5.0% [49] in 18 ASC and hospital-based studies, and we assumed reaspiration was needed for incomplete abortion in two of these studies [40,43].…”
Section: Repeat Aspirationmentioning
confidence: 95%
See 2 more Smart Citations
“…In 14 office-based studies, <0.1% [30] to 8.0% [22] of abortions required repeat aspiration, primarily for retained products of conception, although Thonneau et al [24] did not explicitly report this intervention for the 14 women with retained tissue at follow-up (Table 2). Repeat aspiration ranged from 0% [57] to 5.0% [49] in 18 ASC and hospital-based studies, and we assumed reaspiration was needed for incomplete abortion in two of these studies [40,43].…”
Section: Repeat Aspirationmentioning
confidence: 95%
“…of women were hospitalized for suspected retained products of conception provided few details on the complications involved in these cases, making it difficult to determine whether hospitalbased care was necessary [18,30]. The majority of hospital-based studies reported ≥1.0% of women hospitalized for complications, and many were conducted in Scandinavian countries in the 1980's and early 1990's.…”
Section: Hospitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty percent of women abort within 48 hours, with a procedure-related success rate of around 94%. 5,6 Methotrexate has been used either on its own or in combination with misoprostol to induce abortions at fewer than 7 weeks gestation with a success rate of 90%. The mean injection to abortion period ranges from 11 to 23 days.…”
Section: Discussionmentioning
confidence: 99%
“…The mean injection to abortion period ranges from 11 to 23 days. 6 One must bear in mind that to perform a successful MEA, the cervical canal needs an initial dilation to 9 mm. Our inability to dilate the cervix during the surgical termination may thus point to the likelihood of postablative scarring in the cervical canal.…”
Section: Discussionmentioning
confidence: 99%